2017
DOI: 10.1590/18069657rbcs20160288
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Uptake and Removal by Potato Cultivars as Affected by Phosphate Fertilization of Soils with Different Levels of Phosphorus Availability

Abstract: How to cite: Fernandes AM, Soratto RP, Souza EFC, Job ALG. Nutrient uptake and removal by potato cultivars as affected by phosphate fertilization of soils with different levels of phosphorus availability. Rev Bras Cienc Solo. 2017;41:e0160288.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 29 publications
4
34
0
3
Order By: Relevance
“…Evidence suggests that P is accumulating in some cropland soils (Yuan et al, 2018; Figure 7), which increases uptake by crop plants that may increase P concentrations in food and therefore dietary intake. Some studies have reported high levels of P uptake by crops (Fernandes, Soratto, Souza, & Job, 2017;Gomez, Magnitskiy, & Rodriguez, 2019;Selles, McConkey, & Campbell, 1999;Zhang, Greenwood, White, & Burns, 2007) and non-crop plants (Da Ros, Soolanayakanahally, Guy, & Mansfield, 2018;Ostertag, 2010;Xu & Timmer, 1998) under high soil P concentrations. However, the potential relationship between the global accumulations of P in crop soil and P concentrations in the food produced and subsequent consequences on human health are currently unknown.…”
Section: Human Healthmentioning
confidence: 99%
“…Evidence suggests that P is accumulating in some cropland soils (Yuan et al, 2018; Figure 7), which increases uptake by crop plants that may increase P concentrations in food and therefore dietary intake. Some studies have reported high levels of P uptake by crops (Fernandes, Soratto, Souza, & Job, 2017;Gomez, Magnitskiy, & Rodriguez, 2019;Selles, McConkey, & Campbell, 1999;Zhang, Greenwood, White, & Burns, 2007) and non-crop plants (Da Ros, Soolanayakanahally, Guy, & Mansfield, 2018;Ostertag, 2010;Xu & Timmer, 1998) under high soil P concentrations. However, the potential relationship between the global accumulations of P in crop soil and P concentrations in the food produced and subsequent consequences on human health are currently unknown.…”
Section: Human Healthmentioning
confidence: 99%
“…The 12‐h priming procedure resulted in a large increase in Zn content (Fig. ), compared to the values found in the literature . However, considering the linear adjustment obtained in the cortex of the tubers (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…2), compared to the values found in the literature. 9,14,27 However, considering the linear adjustment obtained in the cortex of the tubers (Fig. 2) and the inexistence of any published work using this method for potatoes, priming with Zn may be effective in fortifying tubers using shorter times than those used in this study.…”
Section: Discussionmentioning
confidence: 72%
“…The response of the application of P in the total dry mass of the potato genotypes was defined by the propagative origin of the plants. Um fornecimento balanceado de nutrientes para a cultura da batata pode proporcionar maior absorção de P pelas plantas, maior rendimento de matéria seca e também pode interferir na maior absorção de outros nutrientes, que conjuntamente com o P, podem conferir aumento de produtividade (FERNANDES et al, 2017).…”
Section: Introductionunclassified